Investigations on the preparation of ceramsite from petrochemical excess sludge - Liu, Zhengwei; Zhang, Hai; Lin, Xiaoyu; Zhang, Hongzhe; Zhang, Zhiyuan; Zhang, Shucai (Frontiers in Chemistry, 2022)
Petrochemical excess sludge, as hazardous solid waste, poses a great threat to the environment and is difficult to dispose of in an economic and environmentally friendly way. A new alternative of using the petrochemical excess sludge to prepare ceramsite is proposed. The relationship between the sintering behavior of dried excess sludge, including the composition, temperature, fluxing agent, and pore-forming agent addition, and the properties of ceramsite is investigated. The properties of ceramsite are primarily affected by the sintering temperature and the addition of a fluxing agent. Ceramsite with a sintering-expanded surface is prepared. Also, its water absorption is quite low, indicating an improvement in densification due to sintering. Moreover, the leaching toxicity of the heavy metals in the dried excess sludge and prepared ceramsite is also investigated. It reveals the feasibility of ceramsite preparation by sintering petrochemical excess sludge.